The routledge international handbook of critical education - Apple, Michael W.; Au, Wayne; Gandin, Luis Armando (Routledge, 2009)
The Routledge International Handbook of Critical Education is the first authoritative reference work to provide an international analysis of the relationship between power, knowledge, education, and schooling. Rather than focusing solely on questions of how we teach efficiently and effectively, contributors to this volume push further to also think critically about education's relationship to economic, political, and cultural power. The various sections of this book integrate into their analyses the conceptual, political, pedagogic, and practical histories, tensions, and resources that have established critical education as one of the most vital and growing movements within the field of education, including topics such as:\social movements and pedagogic work ; critical research methods for critical education ; the politics of practice and the recreation of theory ; the freirian legacy.\With a comprehensive introduction by Michael W. Apple, Wayne Au, and Luis Armando Gandin, along with thirty-five newly-commissioned pieces by some of the most prestigious education scholars in the world, this Handbook provides the definitive statement on the state of critical education and on its possibilities for the future.